2010
DOI: 10.1172/jci39434
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte PDGFR-β signaling is an essential component of the mouse cardiac response to load-induced stress

Abstract: PDGFR is an important target for novel anticancer therapeutics because it is overexpressed in a wide variety of malignancies. Recently, however, several anticancer drugs that inhibit PDGFR signaling have been associated with clinical heart failure. Understanding this effect of PDGFR inhibitors has been difficult because the role of PDGFR signaling in the heart remains largely unexplored. As described herein, we have found that PDGFR-β expression and activation increase dramatically in the hearts of mice expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
140
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 55 publications
6
140
0
Order By: Relevance
“…39,40,45 Kerkela et al 40 demonstrated that the cardiotoxicity of TKIs was an unanticipated side effect of inhibition of c-Abl, a common characteristics of TKIs used in the treatment of CML. In addition, Chintalgattu et al 46 reported that cardiomyocyte platelet-derived growth factor receptor-beta is a regulator of the compensatory cardiac response to pressure overload-induced stress, suggesting that inhibition of platelet-derived growth factor pathway may be at least in part responsible for cardiotoxicity due to TKIs. Accumulated evidence indicates that receptors of tyrosine kinases (RTKs) play an important role in the pathogenesis of PAH, and inhibition of some specific RTK signaling may represent an attractive treatment for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…39,40,45 Kerkela et al 40 demonstrated that the cardiotoxicity of TKIs was an unanticipated side effect of inhibition of c-Abl, a common characteristics of TKIs used in the treatment of CML. In addition, Chintalgattu et al 46 reported that cardiomyocyte platelet-derived growth factor receptor-beta is a regulator of the compensatory cardiac response to pressure overload-induced stress, suggesting that inhibition of platelet-derived growth factor pathway may be at least in part responsible for cardiotoxicity due to TKIs. Accumulated evidence indicates that receptors of tyrosine kinases (RTKs) play an important role in the pathogenesis of PAH, and inhibition of some specific RTK signaling may represent an attractive treatment for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…2008; Chintalgattu et al. 2010). Sham‐operated EC‐MR +/+ and EC‐MR −/− mice underwent the same procedure but without constriction.…”
Section: Methodsmentioning
confidence: 99%
“…Others demonstrate mild symptoms which may be difficult to differentiate from fatigue due to the TKI or the tumor itself (20). This toxicity is not completely understood, but platelet-derived growth factor receptor-β (PDGFR-β) inhibition has been implicated as playing a role in the response to pressure overload-induced stress (21).…”
Section: Adverse Eventsmentioning
confidence: 99%